Role of the Gut Microbiota in Glucose Metabolism During Heart Failure - Bao, Pei; Zhang, Zhiwei; Liang, Yixiu; Yu, Ziqing; Xiao, Zilong; Wang, Yucheng; Yu, Yong; Liu, Wen; Chen, Xueying; Huang, Zhenzhen; Su, Yangang; Chen, Ruizhen; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Glucose metabolism disorder is prevalent in Heart failure (HF), while gut microbiota influences host metabolism by its product. Here, we used the HF model mice and fecal microbiota transplantation (FMT) mice to evaluate the effect of gut microbiota on glucose metabolism during HF. Methods: Thoracic aortic constriction（TAC） surgery was used to establish HF model, part of the surgery mice were treated with antibiotic cocktails per month to clear the microbiota. Blood glucose, intravenous glucose tolerance test (IGTT), insulin and glucagon were measured. 16S rRNA and metabolomics were used to evaluate the change in gut microbiota structure and metabolism. Another group of FMT mice were established to observe the effect of gut microbiota on the host metabolism. The main functional microbiota and metabolism were screened. Results: After bacterial clearance, glucagon, HOMA-IR and the area under the curve (AUC) of IGTT declined significantly in the TAC group at the third month after surgery. 16S RNA indicated that gut microbiota structure altered after TAC surgery, manifested as Firmicutes/Bacteroidetes (F/B) ratio elevated. The fecal metabolomics suggested that noradrenergic (NA) and adrenergic (A) enriched in the TAC group. The FMT mice that transplanted with the fecal of the TAC mice displayed a higher IGTT-AUC, accompanied with higher level of glucagon, insulin and HOMA-IR. The serum metabolomics of the FMT-TAC group showed the gluconeogenesis materials and NA level enriched significantly. Conclusion: The gut microbiota and its metabolism were altered during HF, which have effect of elevating blood glucose and glucagon in the host.